Highly selective biocatalytic synthesis of monoacylglycerides in sponge-like ionic liquids. Issue 2 (5th September 2016) - Lozano, Pedro; Gomez, Celia; Nieto, Susana; Sanchez-Gomez, Gregorio; García-Verdugo, Eduardo; Luis, Santiago V.
Abstract : Monoacylglycerides are biocatalytically synthesized by direct esterification in sponge-like ionic liquids with high selectivity ( e.g. up to 100% monolaurin in [C12 mim][BF4 ]). Abstract : The biocatalytic synthesis of monoacylglycerides (MAGs) was carried out by the direct esterification of fatty acids ( i.e. capric, lauric, myristic, palmitic and oleic acids, respectively) with glycerol in different ionic liquids (ILs) based on cations with long alkyl side-chains ( e.g. 1-hexadecyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide [C16 mim][NTf2 ], 1-dodecyl-3-methylimidazolium tetrafluoroborate [C12 mim][BF4 ], etc .). Although all ILs have been shown as suitable reaction media for Novozym 435-catalyzed esterification of glycerol with free fatty acids, a high selectivity of MAGs was only observed in the [C12 mim][BF4 ] case ( e.g. up to 100% selectivity and 100% yield for monolaurin). Furthermore, as these ILs are temperature switchable ionic liquid/solid phases that behave as sponge-like systems, a straightforward protocol for IL-free MAG recovery, based on iterative centrifugations at controlled temperature, has been developed.